Экология мухоловки малой — Ficedula parva parva (Bechst.) (Aves, Muscicapidae) на Северо-Западном Кавказе - Пекло, А.М.; Ломадзе, Н.X.; Бахтадзе, Г.Б.; Казаков, Б.А.; Тильба, П.А. (Вестник зоологии, 1978)
Nests clutches, nestling growth since the hatching moment till flying out of the nest are described. Data on parents' activity and their behaviour near the nest in the period of feeding the nestlings are presented.